Aniline tetramer-graphene oxide composites for high performance supercapacitors - Yan, Jian (2015)
Polyaniline (PANI), a promising conducting polymer for supercapacitor, exhibits high specific capacitance and good rate capability. However, it suffers from low cycling stability due to the breakage or scission of polymer chains and loss of contact caused by the volume change during the charge–discharge, as well as the irreversible oxidation and reduction. Here, a strategy for using aniline tetramers loaded on graphene oxide (AT-GO) is developed to prevent chain breaking and increase the tolerance of volume change. The potential window is also controlled to reduce the irreversible reactions. In a three electrode test, AT-GO exhibits a good cycling stability with specific capacitance remaining more than 93 to 96% after 2000 cycles. In a two electrode test, the specific capacitance remains 97.7% of its initial specific capacitance after 2000 cycles by suppressing the side reactions. AT-GO also shows a high specific capacitance of more than 769 F g−1 at 1 A g−1 and it remains 581 F g−1 at 60 A g−1, suggesting a good rate capability. These results suggest that AT-GO is a promising electrode material for practical applications.